EVALUATION OF ONLINE LEARNING MATERIALS DEVELOPMENT OF BIPA USING THE CIPP EVALUATION MODEL - Mahda Haidar Rahman; Wagiran Wagiran; Subyantoro Subyantoro (Jurnal Pendidikan Edutama, 2022)
During the pandemic, lectures that were originally conducted face-to-face switched to online, including learning the development of BIPA teaching materials based on the destination country. This change certainly brings several impacts that affect the lecture. Therefore, it is necessary to evaluate learning. The evaluation used is the CIPP evaluation model. The CIPP evaluation model is known as formative evaluation with the aim of making decisions and improving the program. The purpose of this research is to find out how effective the online learning of developing BIPA teaching materials is based on the destination country. This research is an evaluative research that uses a qualitative descriptive approach. The data in this study are primary and secondary data. Data was collected by using interview and questionnaire techniques. Overall aspects of the evaluation of the CIPP model as a result of this study are 1.5% very ineffective, 16.15% ineffective, 55.52% effective and 26.35% very effective. From this percentage, it can be seen that this lecture has been effective, but there needs to be improvements and developments to make it better.